Analysis of the Potential Development of Salt Pond Agroindustry (Case Study in Asempapan Village, Pati Regency) - Amrillah, Rodif; Hanifati, Felsa Naqiba; Pratama, Maulana Daffa Aqila; Aziiz, Ibnu Abi Thoriq (Generasi Sains Indonesia, 2025)
This study analyzes the potential for developing a salt pond agroindustry in Asempapan Village, Pati Regency. The main focus of the study is to evaluate the effectiveness of sales distribution and salt trade channels, considering the imbalance in sales between different pond areas even though the pond area continues to increase. The research method used is descriptive qualitative, with data collection through observation, interviews, literature studies, and documentation. This study explores the concept of agroindustry, characteristics of salt ponds, and the role of government in regulating the salt market mechanism. The discussion includes types of salt, production processes, and challenges and opportunities in developing the salt agroindustry in Asempapan Village. The salt pond industry in Asempapan Village, Pati Regency, shows great potential but faces challenges such as climate change and distribution inequality. Technology development, product diversification, human resource development, market expansion, and price stabilization are needed to increase competitiveness. Government policy support and multi-party collaboration are essential to create an ecosystem that supports the sustainability of this industry, including protecting small farmers from the dominance of large companies. The results of this study are expected to provide insight into optimizing the potential of salt ponds and improving the welfare of salt farmers in the region.